Editorial - Munyangeyo, Théophile; Pichette, François (Studies in Second Language Learning and Teaching, 2012)
New communication and information technologies are probably the main feature associated with the phenomenon of globalisation. Such technologies allow people to be in contact with almost anyone anywhere, raising debates about both their benefits and negative consequences. It is often argued that they contribute to increasing the domination of a few major languages chosen to mediate communication, at the expense of more minor languages in terms of the number of speakers and social status. On the contrary, it is also argued that they allow speakers of minority languages to be in contact with one another and create social networks that may promote the survival, birth, or spread of such languages. The facilitated use of languages over large areas of the world may trigger language differentiation, eventually contributing to the rise of different dialects, or even languages. Among the benefits associated with new technologies, we realise that they give us access to immense language corpora that often reflect language differentiation.